Printed microwave wideband passive balun - Sheikh Fadzullah, Faridah Hanim (2005)
Balun is an important component in a wireless communication system, particularly in a microwave circuit. Its ability to accept an unbalanced input and produce balanced output makes it applicable in various wireless communication application. In this thesis, balun is used as a transformer and an impedance match for a wideband application. Planar balun is chosen over other types of balun because it has some good qualities such as low insertion loss and wide bandwidth. Coplanar waveguide and coplanar strip lines are used to design the balun. The balun transform the unbalanced CPW feed line to balanced CPS feed line. The baluns are design to operate at centre frequency of 3 GHZ. The impedance match between the cable and the balun is obtained using Chebyshev and Binomial multisection impedance transformer. An analysis using MathCAD of balun performance using the two impedance matching theories for three, four and five sections transformers are made. Results show that Chebyshev response has wider wideband bandwidth compare to Binomial response and the more the number of sections, the larger the bandwidth. The wideband transition from CPW to CPS is accomplished through slots in between the two structures. A rectangular slot is introduced to compare the results with other types of slot found in the literature review. The balun is intended to be used for spiral antenna.